Telecommunications networks and services in Estonia. Lessons to other European countries. - Lauri Dieter Frank; Sarolta Németh (European Regional Science Association (ERSA), 2004)
Estonia has shown somewhat remarkable developments in the telecommunications – or more precisely, building up an efficient network of modern information and telecommunications technologies (ICTs) for the Information Society. This paper takes a look at the development of telecommunications infrastructure networks and services in Estonia. The study also evalu-ates what other countries could learn from Estonia. More specifically, by this study we at-tempt at answering whether Estonia is as successful as data suggests, what the factors behind this success are, and whether there are lessons to be learned for the entire European territory. The paper introduces to the development of the telecommunications infrastructure and ser-vices in Estonia, by presenting facts and figures, and comparing the progress of the country with that of other European countries. It also discusses the measures that have helped Estonia on the road to Information Society. The results show that in summary the success of Estonia seems to have been a result of three things: Proximity of Finland and Sweden, active regula-tion and relative early liberalization, and a competition and entrant friendly market environ-ment. The paper is an outgrowth of the ESPON (European Spatial Planning Observation Net-work) project 1.2.2 “Telecommunications Services and Networks: Territorial Trends and Ba-sic Supply of Infrastructure for Territorial Cohesion” (see: http://www.espon.lu).
Keywords: 330